Enhancing Customer Satisfaction and Loyalty at The Walking Drums Ancol: a Strategic Approach - Yusalia Indah Nabila (Publikasi Indonesia, 2025)
This study aims to analyze customer satisfaction and loyalty at Walking Drums Ancol through a strategic marketing approach. The increasing number of cafes in Jakarta has led to intense competition, making customer satisfaction and loyalty essential for business sustainability. This research employs a quantitative approach using survey methods and statistical analysis with SmartPLS software. The study focuses on the influence of the 7P marketing mix—Product, Price, Promotion, Place, People, Process, and Physical Evidence—on customer satisfaction and loyalty. The results indicate that Physical Evidence, Process, and Promotion significantly impact customer satisfaction, while People, Price, and Place show no significant effect. Similarly, Physical Evidence and Process significantly influence customer loyalty, whereas People, Price, Place, and Promotion do not show a strong relationship. The findings highlight the importance of service quality, a seamless customer experience, and strategic promotional efforts in enhancing customer satisfaction and loyalty. This research provides valuable insights for café businesses in Jakarta to refine their marketing strategies and improve long-term customer retention.